Evaluation of the role of metabolites in the diagnosis of the brain tumors using the MRS of the intensified nuclear magnet - Changizi, Vahid; Azarakhsh, Farahnaz; Pooladi, Mehdi (Archives of Advances in Biosciences, 2015)
Nowadays brain tumors remain as a significant cause of morbidity and mortality and are often treatment refractory. The grading of brain tumor has an important implication in clinical management. Currently, magnetic resonance spectroscopy (MRS) is an important modality in evaluating and grading brain tumors. The aim of this study is evaluation of metabolites in the differentiation of brain tumors and grading of brain gliomas using HMRS (proton magnetic resonance spectroscopy).The studies were performed using single voxel MRS ،3Tesla with pulse of sequence used for MRS was point resolved single volume spectroscopy (PRESS)with repetition time (TR) 1000-6000ms and echo time (TE) 36-136ms and The detected distinguished metabolites was included Choline (Cho), Creatin (Cr), and N-acetyl a aspartate (NAA), 37cases had data which passed quality control. The Patient ages ranged from 7 To 81 years, 17 were male and 20 female.MRS data was processed using SYNGO software to give mean spectra and metabolite concentrations which were compared using min it a band SPSS. To test the primary hypothesis, univariate logistic regression was performed on each individual measured metabolite quantity. Significant differences were found in concentrations of key metabolites and Cho/NAA and Cho/Cr ratios using T-test and significance (P≤0.05). In the assessment of age rate and tumor grading, the malignancies of brain tumors did not correlate with patients’ ages as well as sexuality. MRS can detect subtle differences between low grade brain tumors in children and should form part of the clinical assessment of these tumors.